Proposed Integrated Marketing Strategy for NahlaFashion.com - Johara, Ace; Aldianto, Leo (The Indonesian Journal of Business Administration, 2014)
Abstract â€“ The increasing number of Internet users in Indonesia led to many online business opportunities, Muslim fashion online store is one of them. Nahla Fashion, Muslim fashion online store, established on November 4, 2009 with the main business is selling various brands of Muslim Fashion through online media such as: Facebook and Website. Currently, Nahla Fashion faces two main problems: decreasing of sales and online promotion problems. To find out the root of the problems faced by Nahla Fashion, the study conducted using quantitative approach such as: sales database and qualitative approach such as: customer experience questionnaire survey. The decreasing of sales was analyzed by using segmenting, targeting and positioning (STP) and the 4Ps (product, price, place and promotion). While online promotion problem is analyzed by using customer experience surveys and web analytics. From those analysis obtained three main root causes: simple marketing strategy approach, bad Content Management System (CMS) of website and no website optimization with SEO techniques. To solve the problems faced by the proposed Integrated Marketing Strategy, a combination of online marketing strategy and offline marketing strategy (brick and mortar). For online marketing strategy is to sharpen STP strategy and 4Ps strategy. In addition to the proposed changes Content Management System of NahlaFashion.com website and optimization with SEO techniques to increase SERP rankings (search engine results pages) for some targeted keywords on Google. For offline marketing strategy, it is suggested to build an offline store with the new STP and The 4Ps same with online store. Implementation plan is divided into two categories: short term strategic plan is to implement an online marketing strategy and the long term plan for implementing of offline marketing strategy.Â Keywords: Online store, Internet marketing, Web analytics, Brick and mortar, Integrated Marketing Strategy